Terroryzm z perspektywy nauczania trzech papieży — Jana Pawła II, Benedykta XVI i Franciszka - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of this study was to indicate the position taken on the phenomenon of terrorism in the teaching of the Catholic Church by three popes: John Paul II, Benedict XVI and Francis. It has been found that, apart from the common, unambiguously negative assessment of the analysed phenomenon by the hierarchy of the Church, each of them sets out his own observations on its nature and causes. In the teaching of John Paul II, the predominant conviction is that terrorism is an ideology of violence which spreads on the basis of technological and economic development and brings chaos on both a political and personal level. Benedict XVI states that terrorism promotes a civilisation of destruction, which above all questions the dignity of the individual, seeking their annihilation. Pope Francis, on the other hand, focuses on stressing the need for intercultural and interreligious dialogue in order to reduce the growing tensions that are the source of terrorist acts. All the Fathers of the Church, however, draw attention to the fundamental problem of the instrumental treatment of human life by terrorist organisations, for which human beings become a mere means to achieve their various aims.
Keywords: terroryzm; ideologia; religia; Jan Paweł II (papież; 1920-2005); Benedykt XVI; Franciszek (papież)